Flame Response to Equivalence Ratio Fluctuations — Relationship between Chemiluminescence and Heat Release. (December 2013) - Shreekrishna,; Acharya, Vishal; Lieuwen, Tim
This paper presents a comparative study of the global responses of heat release and chemiluminescence emissions of a laminar premixed flame excited by oscillations in fuel/air ratio. Chemiluminescence fluctuations are a commonly used marker of heat release oscillations in unsteady flames. While there is strong evidence of a good correlation between these two quantities in situations where the flame is excited by velocity oscillations, the situation is less well understood for cases where the excitation is due to fuel/air ratio oscillations. This is due to the fact that chemiluminescence is not only a function of the heat release rate, but also a strong function of the fuel/air ratio itself. This work attempts to assess this issue by theoretically evaluating linear transfer functions for the global chemiluminescence and heat release responses of the flame. It is shown that they are qualitatively similar in all cases, but that there are quantitative differences between the two that depend upon operating conditions, nominal flame geometry, and which radical species is being measured.